Peran Mahasiswa Muslim Dalam Mengembangkan Edukasi Agama - Faris Yasin Rochmatullah; Salma Putria Nabila; Aldina Setianingrum; Aisyah Putri Reformasi; Alifah Azatil Ismah; Erwin Kusumastuti (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
This article discusses the important role played by Muslim students in developing religious education, especially in the context of formal and non-formal education. Muslim students have great potential to become agents of change in increasing understanding and appreciation of Islamic teachings in society. With a deep understanding of religious teachings and modern education, they can contribute in various aspects, from direct teaching to developing innovative learning materials. This article also highlights the role of students in religious activities on campus, such as organizing religious studies, religious seminars, and community empowerment programs. Apart from that, Muslim students also utilize information technology and social media to spread religious educational messages widely and effectively. Through these various contributions, Muslim students can help build a society that is more knowledgeable about the Islamic religion, based on inclusive, tolerant values ​​and deep understanding.